Tau Phosphorylation in Female Neurodegeneration: Role of Estrogens, Progesterone, and Prolactin - Muñoz-Mayorga, Daniel; Guerra-Araiza, Christian; Torner, Luz; Morales, Teresa (Frontiers in Endocrinology, 2018)
Sex differences are important to consider when studying different psychiatric, neurodevelopmental and neurodegenerative disorders, including Alzheimer's disease (AD). These disorders can be affected by dimorphic changes in the central nervous system (CNS), and be influenced by sex-specific hormones and neuroactive steroids. In fact, AD is more prevalent in women than in men. One of the main characteristics of AD is the formation of neurofibrillary tangles, composed of the phosphoprotein Tau, and neuronal loss in specific brain regions. The scope of this work is to review the existing evidence on how a set of hormones (estrogen, progesterone and prolactin) affects tau phosphorylation in the brain of females under both physiological and pathological conditions.